2021
DOI: 10.3390/ma14154157
|View full text |Cite
|
Sign up to set email alerts
|

On Incipient Plasticity of InP Crystal: A Molecular Dynamics Study

Abstract: With classical molecular dynamics simulations, we demonstrated that doping of the InP crystal with Zn and S atoms reduces the pressure of the B3→B1 phase transformation as well as inhibits the development of a dislocation structure. On this basis, we propose a method for determining the phenomenon that initiates nanoscale plasticity in semiconductors. When applied to the outcomes of nanoindentation experiments, it predicts the dislocation origin of the elastic-plastic transition in InP crystal and the phase tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The high-pressure phase of InP exhibits metallic properties which contrast the semiconducting nature of the initial B3 phase. The doping of InP crystal affects the pressure of the B3→B1 phase transformation [ 10 , 43 , 44 ]. It was shown that in the InP crystal doped by sulfur, the phase transition occurs in the pressure range from 10.4 to 13.3 GPa [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The high-pressure phase of InP exhibits metallic properties which contrast the semiconducting nature of the initial B3 phase. The doping of InP crystal affects the pressure of the B3→B1 phase transformation [ 10 , 43 , 44 ]. It was shown that in the InP crystal doped by sulfur, the phase transition occurs in the pressure range from 10.4 to 13.3 GPa [ 41 ].…”
Section: Resultsmentioning
confidence: 99%